ANALISIS BUKU GLOBALISASI (JALAN MENUJU KESEJAHTERAAN) DAN KAITANNYA DENGAN PEMBELAJARAN IPS - Supriyanto, Supriyanto; Isbandiyah, Isbandiyah (JURNAL PERSPEKTIF PENDIDIKAN, 2023)
This writing aims to analyze the content of the book “Globalization: Road to Prosperity” and its relevance to social studies education, particularly in preparing social studies teachers to equip themselves as educators teaching social studies from a global perspective. The qualitative method is employed with a literacy study approach. Based on the analysis results, it can be concluded that the book “Globalization: Road to Prosperity” is more applicable to developed countries, while for developing countries, including Indonesia, it is more of a discourse, indicating that although we are in the era of globalization, entering it still requires a considerable amount of time. One notable agreement is that a statement in this book mentions, "Undeniably, we are now in communication, meaning that global communication is deceptive. When the internet is present in a country, it becomes more difficult to control what citizens do with it. However, modern technology is a double-edged sword, making it easier to regulate and monitor specific object movements. In education, facing the era of globalization, educators are responsible for developing and equipping learners with skills and confidence to face increasingly challenging life situations. Social studies educators can incorporate global education into social studies instruction to make learning more meaningful.